Mixed-mode chromatography-mass spectrometry enables targeted and untargeted screening of carboxylic acids in biological samples. Issue 10 (23rd February 2022) - Hodek, Ondřej; Argemi-Muntadas, Lidia; Khan, Adnan; Moritz, Thomas
Abstract : Mixed-mode chromatography method offers quantification of TCA carboxylates in cells, human plasma, and plants. Abstract : Carboxylic acids are crucial metabolites in the tricarboxylic acid (TCA) cycle and thus participate in central carbon metabolism (CCM). Research dependent on the analysis of metabolites involved in central carbon metabolism requires fast separation and sensitive detection of carboxylic acids using liquid chromatography-mass spectrometry (LC-MS). However, successful separation of all carboxylic acids from the TCA cycle by liquid chromatography remains a challenging task because of their high polarity and thus low retention on the conventional reversed-phase columns. In this study, we tested a reversed-phase/anion exchange mixed-mode stationary phase (Waters BEH C18 AX) using liquid chromatography-tandem mass spectrometry (LC-MS/MS). We developed and optimized a method that enables a 10 minute separation of all carboxylic acids from the TCA cycle and lactic acid without prior derivatization or addition of ion-pair reagents in the mobile phase. The developed method was validated for quantification of 8 acids in murine brown preadipocytes, 5 acids in human plasma and 6 acids in Arabidopsis thaliana leaves with limits of quantification ranging from 0.1 μM for malic acid to 10 μM for isocitric acid. Moreover, the mixed-mode chromatography enabled untargeted screening of medium- to long-chain fatty acids in murine brown preadipocytes, Arabidopsis thaliana, and human plasma, where 23 fatty acids were identified by using liquid chromatography with high-resolution mass spectrometry (HRMS).